Seafood procurement auctions in the presence of origin falsification: Price-only auction versus scoring auction - Shangjun Piao; Jiantao Guo (PLoS ONE, 2026)
Origin falsification in seafood procurement is a significant issue that threatens supply chain integrity and distorts market competition. Despite advances in origin detection technologies, this problem persists, particularly when penalty mechanisms lack sufficient deterrent effects and fail to function effectively. In response, this study explores how different auction formats, particularly price-only and scoring auctions, can address this challenge in seafood procurement. To address this issue, we first derive the equilibrium outcomes for both price-only and scoring auctions in the presence of origin falsification. Then, we analyze how origin falsification affects the equilibrium outcomes. Finally, we conducted a comparative study of the two auction formats to explore the best format for seafood purchasers. The results suggest that when the extent of origin falsification is within a certain range, the price-only auction may outperform the scoring auction for the purchaser. This relative advantage appears more noticeable when consumers show stronger preferences for the origin. Additionally, we find that under specific conditions, purchasing seafood from low-value origins may align with purchasers’ interests. From an extended numerical study, when origin detection is available, a positive detection rate reinforces the dominance of price-only auctions in cases of severe falsification. These findings contribute to the literature on procurement auctions by highlighting the need for auction design adjustments to mitigate origin falsification in seafood procurement.